2015
DOI: 10.3991/ijet.v10i2.4355
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gamification on Students’ Motivation in using E-Learning Applications Based on the Motivational Design Model

Abstract: Abstract-Students' motivation is an important factor in ensuring the success of e-learning implementation. In order to ensure students is motivated to use e-learning, motivational design has been used during the development process of e-learning applications. The use of gamification in learning context can help to increase student motivation. The ARCS+G model of motivational design is used as a guide for the gamification of learning. This study focuses on the influence of gamification on students' motivation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 12 publications
(13 reference statements)
0
29
0
8
Order By: Relevance
“…No obstante, los modelos de gamificación vinculados al proceso educativo representan más de la mitad de la muestra de la última criba: 10 artículos (58%), entre los cuales se encuentran: Nolan y McBride (2013); Schoech, Boyas, Black y Lambert (2013); Mettler y Pinto (2015); Hamzah, Ali, Saman, Yusoff y Yacob (2015); Kim y Lee (2015); y Tomé, da Cunha, Farias, Rosa, Anton y Gasparini (2015). No obstante, estos últimos dos modelos mencionados se presentan como los únicos en evidenciar con meridiana claridad su orientación hacia entornos e-learning, demostrando su efectividad frente a entornos de enseñanza tradicional y especificando la proveniencia de cada una de sus variables.…”
Section: Taxonomías De La Gamificación En La Literatura Científicaunclassified
“…No obstante, los modelos de gamificación vinculados al proceso educativo representan más de la mitad de la muestra de la última criba: 10 artículos (58%), entre los cuales se encuentran: Nolan y McBride (2013); Schoech, Boyas, Black y Lambert (2013); Mettler y Pinto (2015); Hamzah, Ali, Saman, Yusoff y Yacob (2015); Kim y Lee (2015); y Tomé, da Cunha, Farias, Rosa, Anton y Gasparini (2015). No obstante, estos últimos dos modelos mencionados se presentan como los únicos en evidenciar con meridiana claridad su orientación hacia entornos e-learning, demostrando su efectividad frente a entornos de enseñanza tradicional y especificando la proveniencia de cada una de sus variables.…”
Section: Taxonomías De La Gamificación En La Literatura Científicaunclassified
“…The effects on the dependent variables mentioned in gamification were explained by the participants from the primary school to undergraduate level so different results were presented. According to the findings, there were significant differences on motivation in seven studies (Chen et al, 2016;Cózar-Gutierrez & Sáez-López, 2016;Fotoris, Mastoras, Leinfeliner & Rosunally, 2016;González et al, 2016;Hamzah et al, 2015;Pesare et al, 2016;Siemens vd., 2015) while no significant difference was found in two studies (Juárez & Carballo, 2016;Roper & Vecera, 2016) Results showed that three out of seven studies had positive effect of gamification on learning. However, the rest of four studies had positive results (e.g.…”
Section: öNerilermentioning
confidence: 99%
“…Game elements were implemented to the classroom settings with and without the help of technological tools. Some research studies were defined themselves as game based learning studies, however they were actually gamification applications because there was no game used within the studies (Chen et al, 2016;Cózar-Gutierrez & Sáez-López, 2016;González et al, 2016, Hamzah et al, 2015Pesare et al, 2016;Siemens et al, 2015).…”
Section: öNerilermentioning
confidence: 99%
“…In recent years, the ARCS model has been variously applied to investigate whether it enhances learning motivation, and the results have generally been positive (Alhazbi, 2015;Hamzah et al, 2015;Kaneko et al, 2015;Qian, 2014;Yurdaarmagan et al, 2015;Peng, Liu, & Liu, 2016). For example, Zhang (2017) designed a micro-lecture teaching platform based on ARCS model theory.…”
Section: Arcs Modelmentioning
confidence: 99%